USING GAMES AND PLAY-BASED LEARNING TO MOTIVATE PRIMARY STUDENTS IN ENGLISH LESSONS - Jovliyeva Nafosat Bahodir qizi (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Annotation: This article explores the role of games and play-based learning in motivating primary school students to learn English. It highlights how interactive, fun, and engaging classroom activities can enhance students’ interest, participation, and achievement in language learning. The study emphasizes that play-based methods stimulate emotional and cognitive involvement, promote collaboration, and reduce anxiety among young learners. The findings suggest that integrating games into English lessons not only improves vocabulary and speaking skills but also develops creativity, problem-solving ability, and positive attitudes toward learning English.